Substitution and Positional Reversal in the Marginal Notes of (The Divine Conquests with an Explanation of Al-Jalalayn's Interpretation of the Hidden Subtleties): A Descriptive Analytical Study - كريم, بيستون علي; أحمد, فهمي كريم (Sulaimani Journal for Humanities, 2019)
When a literary text, art text or any texts that have been written by humankind are worth many different interpretations and studies, but what if that text has been descended by the Creator of the universe, how many different translations and studies that text worth making? Doubtlessly, we all know that the Holy Quran is one ot those texts, so long the life continues, would be possible to be researched and analyzed without reduction of its ́ significance. Therefor the researcher selected one of the Holy Quraans ́ interpretation named (ALftwhat ALelahyia) which was written by shekh Sulaiman Omer, known as (ALjamal). His interpretation is full of lingual thoughts are worth to be researched accurately. The researcher has selected a subject from that interpretation to research. The subject is (ALibdal wa ALlqalb ALmakani) which is composed of two topics on phonology. The researcher has tried to analyze ALjamals ́ thoughts depending and referring to the basics of those thoughts from the old and new lingual books.